A Screening Test for Iron Deficiency Anaemia and Thalassaemia Traits - Kabir, Amin Lutful; Dipta, Tashmim Farhana; Khatun, Hajera; Rahman, Mohammad Hafizur; Haq, Mahfuz; Uddin, Mohammad Kazim; Begum, Masuda (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Both iron deficiency and thalassaemia trait can present with hypochromic microcytic morphology. Naked eye single tube red cell osmotic fragility (NESTROF) is an inexpensive and simple test which can effectively differentiate iron deficiency anaemia from thalassaemia trait. Our study was an opportunity to observe the role of NESTROF in screening of thalassaemia trait among our study population. Initially NESTROF was carried out in 677 patients (N) population of four groups having both positive and negative NESTORF; for economical issue, auto-analyzer study and haemoglobin electrophoresis were done among only 100 randomly selected subjects, who were finally included in our study as final study population (n). In our study, NESTROF was 94.23% sensitive and its specificity was 92.08%. The predictive value of a positive test was 88.13% and predictive value of a negative test was 96.24%. Our study showed, NESTROF can effectively differentiate iron deficiency anaemia (IDA) from thalassaemia trait but, is not effective in co-existent IDA and thalassaemia. J Bangladesh Coll Phys Surg 2014; 32: 190-193